11. CLINICAL AND PARACLINICAL CHARACTERISTICS NEUTROPHIL-TO-LYMPHOCYTE RATIO CHANGES, AND THEIR ASSOCIATION WITH TREATMENT OUTCOMES IN MULTIPLE TRAUMA PATIENTS AT MILITARY HOSPITAL 175 (Vietnam Journal of Community Medicine, 2025)
Objectives: To identify the clinical and paraclinical characteristics and the relationship between the change in neutrophil/lymphocyte ratio (NLR) and treatment outcomes in trauma patients treated at Military Hospital 175.Method: A descriptive, longitudinal study on 60 trauma patients who was diagnosed according to the Berlin criteria of 2014 at Military Hospital 175 from June 2024 to May 2025. Data were collected at the following time points: T0 (admission), T1 (24 hours after admission), and T2 (48 hours after admission).Results: The majority of patients were male (73.3%), with 86.7% aged between 20 and 60 years, and the main cause was traffic accidents (81.7%). The most common injuries were chest trauma (80%) and traumatic brain injury (61.7%), with 40% of patients sustaining injuries to two organ systems. The median duration of mechanical ventilation and hospital stay were 4 days and 10 days, respectively. The mortality rate in the study population was 28.3%. The NLR value at admission for the survival and death groups were 9.86 and 15.3, respectively. The NLR at admission has predictive value for mortality in trauma patients, with an area under the curve (AUC) of 0.774, p < 0.05, and a cut-off point of 8.32 with sensitivity Se = 100% and specificity Sp = 46%.Conclusion: Trauma patients treated at Military Hospital 175 are primarily male, of working age, due to traffic accidents. Chest trauma and traumatic brain injury are the two most common injuries. The NLR value at admission has prognostic significance for mortality in trauma patients
Keywords: Multiple trauma; neutrophil-to-lymphocyte ratio.